2001
DOI: 10.1097/00007890-200107270-00019
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Hepatitis a Vaccination in Liver Transplantation Recipients1, 2

Abstract: HAV vaccination is safe in OLT recipient. Efficacy of HAV vaccination in OLT recipients, as measured by a commercially available enzyme immunoassay, is low and alternative strategies should be developed to improve response rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 21 publications
4
31
0
7
Order By: Relevance
“…43,44 Although the HAV vaccine is also safe in patients with decompensated disease and in liver transplant recipients, the immunogenicity of the vaccine is substantially lower than in those with compensated liver disease. 42,45,46 Therefore, early vaccination against HAV is important in patients with chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Although the HAV vaccine is also safe in patients with decompensated disease and in liver transplant recipients, the immunogenicity of the vaccine is substantially lower than in those with compensated liver disease. 42,45,46 Therefore, early vaccination against HAV is important in patients with chronic liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Recently there was an important change in the seroconversion rates [28][29][30][31] (Table 2). The response of patients with decompensated chronic hepatic disease is known to be lower, with lower antibody levels and lower seroconversion rates, when compared to those with compensated disease.…”
Section: Hepatitis a Vaccinementioning
confidence: 99%
“…Although there are no studies regarding immunogenicity of this vaccine among PSCT recipients, it has been shown to be safe and immunogenic in other immunocompromised hosts. [23][24][25][26][27] In conclusion, 14% of nonvaccinated anti-HAV seropositive patients can lose these antibodies 1 year following PSCT. We recommend immunizing these patients.…”
Section: Discussionmentioning
confidence: 84%